Pengaruh UMP, PDRB, dan investasi terhadap penyerapan tenaga kerja industri di Pulau Jawa - Desy Meilasari (FEBI IAIN Langsa, 2020)
This research aims to analyze the effect of provincial Minimum wage (UMP), PDRB, and investment in the industrial sector of labor absorption on Java island in 2010-2016. Data used is a data panel consisting of data time series 2010 – 2016 and cross section six provinces namely DKI Jakarta, West Java, Central Java, IN Yogyakarta, East Java, and Banten. The Anaalisis tool used is a data regression panel i.e. Fixed Effect Model (FEM). The results showed that UMP has a significant effect on the labor absorption of the industrial sector on Java Island in 2010-2016. While the PDRB and investment have a positive and significant effect on the labor absorption of industrial sectors in Java Island in 2010-2016. Through this research, the government expects more cautious and creating a conducive investment climate so that the value of PDRB is increasing.